Pluralitas Dalam Teori Perencanaan - Priyani, Rina (Journal of Regional and City Planning, 2007)
Pluralism is nothing new but plurality approach in planning theory is  a  recent  reaction  to  the  failture  of  rational  comprehensive planning. Planning itself is considered to be “a good planning” if  it  could  accommodate  the  plurality.  The  idea  of  plurality  c an  be explored   in  diversity  and  difference  concepts  as  coined  by Sandercock.  This  article  aims  to  discuss  plurality  in  planning theory  using  the  phenomenon  of  urban  heritage  as  one  of multicultural  city‟s  assets.  Opportunity  and  limitation  indeveloping  the  concepts  are  discussed  to  emphasize  its contribution to planning theory and practice.